Optimasi Desain dan Analisis Struktur Bracket Kombinasi Menggunakan FEA dan Topology Optimization untuk Kendaraan Hemat Energi - Adrian Fasa Putra; Amrul Khasani; Didin Zakariya Lubis (TURBO [Tulisan Riset Berbasis Online], 2026)
The increasing consumption of fossil fuels in the transportation sector has encouraged the development of energy-efficient vehicles through structural weight reduction. However, previous studies generally optimized axle brackets and brake caliper brackets separately while employing only a single optimization approach. This study proposes an integrated bracket combining both functions through the integration of Aluminum 6061 material selection, wall thickness adjustment, topology optimization, finite element analysis (FEA), and weighted scoring. Topology optimization was performed using a minimize mass objective with a 60% retained mass, producing four design alternatives evaluated based on mass, von Mises stress, deformation, and safety factor. The results indicate that Design 4 achieved the highest weighted scoring value of 0.995 and reduced bracket mass by 43.9% compared with the initial design while maintaining a maximum stress of 38.664 MPa, a maximum deformation of 0.0266 mm, and a safety factor of 2.229. The scientific contribution of this study lies in the development of an integrated bracket evaluated through multiple optimization strategies within a single design framework. Practically, the proposed design has the potential to reduce vehicle weight and support higher energy efficiency in Urban Concept Shell Eco-marathon vehicles.